10x−1=

7x+26

1 answer

To solve the equation \( 10x - 1 = 7x + 26 \), follow these steps:

  1. Rearrange the equation to get all terms involving \( x \) on one side and constant terms on the other side. Subtract \( 7x \) from both sides:

    \[ 10x - 7x - 1 = 26 \]

    This simplifies to:

    \[ 3x - 1 = 26 \]

  2. Add 1 to both sides to isolate the term with \( x \):

    \[ 3x - 1 + 1 = 26 + 1 \]

    This simplifies to:

    \[ 3x = 27 \]

  3. Divide both sides by 3 to solve for \( x \):

    \[ x = \frac{27}{3} = 9 \]

So, the solution is:

\[ \boxed{9} \]